National Health Insurance Membership and Economic Status as Determinants of Accessibility of Antenatal Care Service - Rosidah, Lely Khulafa'ur; Asdary, Rahma Novita (Journal of Maternal and Child Health, 2021)
Background: According to WHO statistics, the maternal mortality rate (MMR) in developed countries is estimated at 12/100,000 live births, while in developing and low-income countries it is 239/100,000 live births. 99% of all maternal deaths are estimated to occur in developing countries, even though the causes of death can be prevented with the right policies considering that one of the goals of the Sustainable Development Goals is to reduce MMR. Antenatal Care (ANC) is the main technique to reduce maternal morbidity and mortality. This study evaluates JKN membership and economic status affecting ANC service coverage. Subjects and Method: This study is a cross-sectional study using data from the 2017 Indonesian Demographic and Health Survey (IDHS). This data is used to assess the proportion of economic status and national health insurance (JKN) membership and to measure the relationship between the two with ANC coverage. Analysis using Logistic Regression with R software version 3.6.3. and perform Propensity Score Matching (PSM) to reduce self-selection bias by balancing the observed variables between groups of respondents based on economic status with and without JKN. Results: Of the 5429 respondents, 20.2% were very poor, 20.9% poor, 19.9% middle class, 20.8% rich, and 18.2% very rich. Among these residents, 61.4% have JKN membership and 38.3% do not. The substantial gap in the utilization of maternal health services, especially in ANC4x services, is 30.7 points between the very poor (48.2%) and the very rich (86.9). Respondents who worked as employees were more likely to have JKN membership than those who did not have a job (AOR=2.34; 95% CI = 1.74 to 3.16). Respondents who were exposed to the internet at least once a week were more likely to have JKN membership than those who were not exposed to the internet (AOR=1.46; 95% CI= 1.09 to 1.97). Conclusion: JKN membership and economic status affect ANC 4x service coverage.